2011
DOI: 10.4103/0970-9185.83675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total intravenous anesthesia using propofol and inhalational anesthesia using isoflurane for controlled hypotension in functional endoscopic sinus surgery

Abstract: Background:An important requirement during functional endoscopic sinus surgery is to maintain a clear operative field to improve visualization during surgery and to minimize complications.Materials and Methods:We compared total intravenous anesthesia using propofol with inhalational anesthesia using isoflurane for controlled hypotension in functional endoscopic sinus surgery. It was a prospective study in a tertiary hospital in India. Forty ASA physical status I and II adult patients (16–60 years) were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 11 publications
5
51
0
Order By: Relevance
“…In one study only the anesthesia personnel assessing intraoperative blood loss was blinded to the type of anesthetic used, not the surgeon. 21 In four studies the surgeon was blinded to the type of anesthetic. Blinding was often performed by having a covered infusion pump for propofol set up in every room and a covered volatile anesthetic vaporizer.…”
Section: Resultsmentioning
confidence: 99%
“…In one study only the anesthesia personnel assessing intraoperative blood loss was blinded to the type of anesthetic used, not the surgeon. 21 In four studies the surgeon was blinded to the type of anesthetic. Blinding was often performed by having a covered infusion pump for propofol set up in every room and a covered volatile anesthetic vaporizer.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the surgeon was more satisfied with the surgical field in the clonidine group than with that in the placebo group. Also Jabalamelli [16] and Masood Mohseni et al [11] reported that bleeding severity was significantly lesser in clonidine group. Similar to our study, they concluded that premedication with oral clonidine 0.2 mg can effectively reduce bleeding during FESS.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been designed to reduce bleeding during surgery, none of these techniques have consistently provided a desirable bloodless field for the surgeon. So to provide optimal field hypotensive agents given such as sodium nitroprusside, nitroglycerine, propofol, clonidine, esmolol, metoprolol & atenolol had been used individually to decrease blood loss in FESS [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies do not show significant difference after excluding the effect of concomitant use of remifentanil [29][30][31] .…”
Section: Choice Of Anaesthetic Agentmentioning
confidence: 98%